DETERMINAN KEJADIAN KECELAKAAN KERJA PADA PETUGAS PENANGANAN PRASARANA DAN SARANA UMUM (PPSU) DI KECAMATAN CEMPAKA PUTIH KOTA JAKARTA PUSAT - Nandha Maylliana Aqsha (2021)
The number of work accidents in Indonesia has statistically decreased. However, DKI Jakarta is still included in the five provinces with the most work accident victims. One of the jobs at risk of having a work accident is the Handling of Public Infrastructure and Facilities (PPSU). The purpose of this study was to determine the determinants of the incidence of work accidents on PPSU officers in Cempaka Putih District, Central Jakarta City. This research is a quantitative analytic study with a cross sectional design. The number of samples as many as 133 people were taken by proportional stratified random sampling technique. Collecting data using interview techniques. The analysis used is Chi-Square and multiple logistic regression. The independent variables in this study were age, gender, years of service, education level, knowledge, supervision, work shifts, unsafe behavior, and unsafe conditions. The results of multivariate analysis showed that there was an increased risk of occupational accidents among PPSU officers who worked under low supervision (OR=2.770; 95% CI=1,300-5.904) compared to high supervision and unsafe conditions (OR=2,328; 95% CI=1,300- 5.043) compared to the safe condition. The advice given to government agencies is that it is expected to increase supervision and the role of supervisors, as well as monitor field conditions on a regular basis.